Financial Reporting in Japan: Regulation, Practice and Environment. - Doupnik, Timothy S. (The Accounting Review, 1993)
Reviews the book "Financial Reporting in Japan: Regulation, Practice and Environment," by T.E. Cooke and M. Kikuya.